America’s Foreign Policy and the Challenges of Liberal Democracy in Africa - Fajimbola, Joshua Olatunde (Journal of Contemporary International Relations and Diplomacy, 2022)
The paper examines the United States of America’s foreign policy toward Africa in terms of promoting liberal democracy, as well as the challenges that African countries face in putting liberal democracy principles into practice, thereby impeding expected dividends and development. It is based on secondary data sources and descriptive data analysis methods. The findings revealed a gap between what the United States proposed for Africa in terms of good governance, anti-corruption, and social development and how liberal democracy actually works on the continent. The paper observed that, despite America’s celebration of liberal democracy, the effect in Africa is contextualized by the majority of African countries’ experiences of impressive governance, ineffective leadership, and endemic corruption. The various bilateral agreements between the United States of America and some African countries to promote liberal democracy have also been called into question due to deviations from expected outcomes. The paper suggests a philosophical approach to liberal democracy in Africa that incorporates pre-colonial African leadership traditions and governance cultures. African governments should invest adequately in youths and galvanize their energies for productivity through employment opportunities in order to uphold and protect liberal democracy. On the other hand, the United States should strengthen bilateral relations with each African country to ensure that they achieve good governance and economic development for mutual benefit.